Review Article Using Fish Bones For Glue (Adhesive) - Amanda, Trisna Rosa; Junianto (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2024)
Apart from being a food/consumer ingredient, fish is also an industrial raw material. In the development of the fishery product processing industry, waste by-products will inevitably be left behind. Waste that is not treated immediately will cause environmental pollution, besides that it will become a source of microbial growth which can harm the body's health. One of the fishery wastes can be fish bones. Efforts to utilize fish bones are processed into fish adhesive/glue. The purpose of this review article is to provide information on the procedure for making glue from fish bones and the characteristics of the glue/adhesive it produces. The method used is by reviewing various national and international journals from 2005 to 2023 regarding the use of fish bone waste as a material for making glue (adhesive). Based on the results of the review, it can be concluded that the procedure for making glue from fish bones consists of the stages of cutting and washing the bones, the extraction process with the acetic acid solution at a temperature of 60 -70oC for 4 - 5 hours, the cooling and filtering process and finally the concentration of the extracted solution. The characteristics of glue from different types of fish bone raw materials did not show significant differences in terms of adhesive strength, wood surface damage, viscosity, poise, and water content. Keywords: adhesive strength, viscosity, water content, extraction, acetic acidAbstrak Abstrak Selain menjadi bahan pangan/konsumsi, ikan juga sebagai bahan baku industri. Dalam perkembangan industri pengolahan hasil perikanan pasti akan menyisakan hasil samping limbah. Limbah yang tidak segera ditangani akan menimbulkan pencemaran lingkungan, selain itu akan menjadi sumber pertumbuhan mikroba yang dapat mengganggu kesehatan tubuh. Salah satu limbah perikanan dapat berupa tulang ikan. Upaya dari pemanfaatan tulang ikan adalah diolah menjadi perekat/lem ikan (fish glue).  Tujuan artikel review ini adalah untuk menginformasikan prosedur pembuatan lem dari tulang ikan dan karakteristik lem/perekat yang dihasilkannya. Metode yang digunakan yaitu dengan menelaah dari berbagai jurnal nasional dan internasional dari tahun 2005 sampai 2023 mengenai pemanfaatan limbah tulang ikan sebagai bahan pembuatan lem (perekat).  Berdasarkan hasil review dapat disimpulkan bahwa prosedur pembuatan lem dari tulang ikan terdiri dari tahapan pemotongan dan pencucian tulang, proses ekstraksi dengan larutan asam asetat pada suhu 60 -70oC selama 4 - 5 jam, proses pendingin dan penyaringan dan terakhir pemekatan larutan hasil ekstraksi.  Karakteristik lem dari bahan baku tulang ikan jenis yang berbeda tidak menunjukkan perbedaan yang signifikan dilihat dari keteguhan rekat, kerusakan permukaan kayu, viskositas, poise, dan kadar air. Kata Kunci: keteguhan rekat, viskositas, kadar air, ekstraksi, asam asetat